Meta-cognitive Therapy in Obsessive Compulsive Disorder: A Case Report - Ayushi Gaur; Shivali Sharma; Shweta Singh (Indian Journal of Psychological Medicine)
Psychotherapeutic developments in the management of anxiety disorders are evolving, with notable evidence in obsessive compulsive disorder (OCD). Third-wave therapies significantly contribute to the reduction in psychopathological symptoms and, thus, provide a positive turning point in the socio-occupational spectrum of the patient. One such third-wave approach is meta-cognitive therapy (MCT), which addresses cognitive attention syndrome (CAS) and directly prohibits ritualistic behavior, thereby decreasing the burden of symptoms. In India, it seems there is a dearth of literature exploring the effectiveness of MCT. The present case report provides a detailed insight into the psychotherapeutic treatment using MCT, in which 10 sessions were provided to an OCD patient along with pharmacotherapy. The treatment shows a noteworthy improvement in thought fusion, obsessional beliefs, meta-cognitive beliefs, and psychopathology. The symptoms gradually waned during the three- and six-month follow-up baseline period. Therefore, the case report demonstrates the effectiveness of combined medication and MCT in treating OCD. Additionally, it shows the potency of MCT in prolonged improvements in cognitive flexibility and inflated feelings of responsibility and perfection.